LONG-TERM HEALTH RISK AFTER BREAST-CANCER RADIOTHERAPY: OVERVIEW OF PASSOS METHODOLOGY AND SOFTWARE. Issue 1 (6th December 2018) - Eidemüller, Markus; Simonetto, Cristoforo; Kundrát, Pavel; Ulanowski, Alexander; Shemiakina, Elena; Güthlin, Denise; Rennau, Hannes; Remmele, Julia; Hildebrandt, Guido; Wolf, Ulrich
Abstract: Breast-cancer radiotherapy reduces the recurrence rates and improves patient survival. However, it also increases the incidence of second cancers and of heart disease. These radiation-induced long-term health risks become increasingly important with improved cure rates and prolonged patient survival. Radiation doses to nearby as well as distant organs strongly vary between different irradiation techniques and among individual patients. To provide personalized lifetime risk estimates, the German national project PASSOS combines individual anatomy, dosimetric estimates, organ-specific low- and high-dose risk models and personal risk factors such as smoking. A dedicated software tool is under development to assist clinical decision-making processes.